2018
DOI: 10.1292/jvms.17-0528
|View full text |Cite
|
Sign up to set email alerts
|

Injury and mechanism of recombinant <i>E. coli</i> expressing STa on piglets colon

Abstract: Enterotoxigenic Escherichia coli (ETEC) is primary pathogenic bacteria of piglet diarrhea, over two thirds of piglets diarrhea caused by ETEC are resulted from STa-producing ETEC strains. This experiment was conducted to construct the recombinant E. coli expressing STa and study the injury and mechanism of recombinant E. coli expressing STa on 7 days old piglets colon. Twenty-four 7 days old piglets were allotted to four treatments: control group, STa group (2 × 109 CFU E. coli LMG194-STa), LMG194 group (2 × 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 30 publications
(28 reference statements)
2
16
0
Order By: Relevance
“…Subsequent qPCR analysis revealed that AQP3 expression in the small intestine of PEDV-infected piglets was extremely significantly downregulated compared with normal piglets, with the most significant decrease in the jejunum tissue. Lv et al reported the same trend of AQP3 expression in the colon of pigs with diarrhea caused by enterotoxigenic E. coli (ETEC) [ 28 ]. Studies have shown that AQP3 expression is competitively regulated by miR-874 and lncRNA H19, which in turn opens the tight junction complex, resulting in decreased occludin and claudin-1 protein expression and increased intestinal permeability [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 93%
“…Subsequent qPCR analysis revealed that AQP3 expression in the small intestine of PEDV-infected piglets was extremely significantly downregulated compared with normal piglets, with the most significant decrease in the jejunum tissue. Lv et al reported the same trend of AQP3 expression in the colon of pigs with diarrhea caused by enterotoxigenic E. coli (ETEC) [ 28 ]. Studies have shown that AQP3 expression is competitively regulated by miR-874 and lncRNA H19, which in turn opens the tight junction complex, resulting in decreased occludin and claudin-1 protein expression and increased intestinal permeability [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, lactoferrin inhibited adherence of ETEC to both human epithelial cells and to the intestinal mucosa of germfree mice (68). Host metal-binding proteins calprotectin, myeloperoxidase, and lactoferrin, typically derived from host neutrophils, have become fecal markers of ETEC infection, and recent studies have shown that these biomarkers can be used to assess the burden of enteric infections (42,65,(69)(70)(71).…”
Section: Figmentioning
confidence: 99%
“…Changes in the architecture of the intestinal tissue included the increase in the number of goblet cells and in the cell density, which in the latter is characterized by volume of the leukocyte infiltrate in the sub-mucosa. The goblet cells are responsible for the layer of mucus that covers the epithelium to facilitate the removal of food content and are also part of the first line of defense against damage caused by pathogenic bacteria and bacterial products 27 , 28 . Here, coinfected mice showed several of these mucoid cells in the enterocyte layer, which indicates that the innate response to the infection bacteria was active in these animals.…”
Section: Discussionmentioning
confidence: 99%